Analysis of the service dominant logic network, authors and articles - Silva, S. V.; António, N.; Crespo de Carvalho, J. (Service Industries Journal, 2017)
The present study analyses research conducted in Service Dominant Logic (S-D logic), providing an overview of its intellectual structure. For that purpose, a structured approach was adopted through the implementation of bibliometric methods, using co-citation analysis combined with performance analysis and an integrative science mapping approach, which considered a timeline, a graph, and a distance-based perspective. This allowed the identification of the leading authors and of six clusters of articles based on bibliographic coupling, along with the most prominent research themes clustered in five subdomains of research based on co-occurrence of terms. The networks extracted show the associations between the main articles and concepts treated by the S-D logic community, unveiling the salient challenges and prospective expansion facing its future theoretical and practical context.